High-overtone mode piezoelectric transformer based on c-axis zigzag ScAlN multilayer for wake-up receiver applications - Sarina Kinoshita; Rei Karasawa; Takahiko Yanagitani (AIP Advances)
The efficiency of RF-to-DC conversion in rectifying antennas in wake-up receivers significantly diminishes at lower RF power levels. In this study, we propose passive high-overtone bulk acoustic wave type piezoelectric transformers composed of an input layer (c-axis tilted ScAlN single-layer)/an acoustic delay-line/an output layer (c-axis zigzag polarization-inverted ScAlN multilayer) to amplify the RF voltage for rectenna applications. To obtain high-Q and high-voltage gain, high-overtone mode, such as over 100th overtone mode, was employed by a high-Q acoustic delay-line between input and output films. The full width at half maximum values of the ψ-scan curves for the input single-layer ScAlN, the odd layers of the output multilayer, and the even layers of the output multilayer were 7.2° at ψ = 39°, 11° at ψ = 44°, and 9.1° at ψ = 45°, respectively, as determined by XRD (0002) pole figure analysis, indicating good crystalline orientation. The thickness-quasi-shear mode electromechanical coupling coefficients k′352 were estimated to be 16.8% for the input single-layer and 6.3% for the output multilayer. The experimental passive voltage gain approaching 12 (+20 dB) in the 500 MHz range in the transformer is observed. The experimental result agreed well with the theoretical prediction simulated by the electromechanical transmission line model considering polarization inversion effect.